Composition of Government Expenditures and Demand for Education in Developing Countries - Matovu, John (IMF Working Papers; Working Paper ;, 2002)
This paper addresses the potential effects on human capital accumulation and economic growth of the alternative compositions of public expenditures in the context of a computable dynamic general equilibrium model of overlapping generations and heterogeneous agents in which altruistic parents make schooling decisions for their children. In the presence of fixed and variable costs for different levels of schooling, we show that reducing household costs of primary education has the largest positive impact on growth and poverty reduction in the short run. Moreover, an increase in higher education spending increases long-run growth. These effects can be substantial even when increasing education spending comes at the expense of public infrastructure investment.